KAJIAN LITERATUR BIOMEKANIKA GERAKAN TEKNIK SHOOTING DALAM SEPAK BOLA - Ghani Yanuaji, Firman; Gumilar , Agus; Darajat Kusumah Negara , Jajat; Nuryadi (Cahaya Ilmu Bangsa Institute, 2025)
Football is one of the most popular sports for people all over the world. In a football game, there are several basic techniques that must be mastered by the players, one of which is shooting technique. This study aims to draw conclusions regarding the most effective biomechanical techniques of shooting in football, as well as provide recommendations for training and improving football players techniques. This research uses a descriptive qualitative approach with a literature review type method. Data processing in this study was carried out by means of selection and content analysis and data analysis techniques using thematic analysis. The data obtained from previous research was analyzed based on the main themes relevant to the biomechanics of movement in football shooting techniques. Based on the results of the study, several factors were found to influence the biomechanics of shooting techniques in soccer, including the angle of inclination of the kick, knee angle, foot structure, anaerobic fatigue, forward swing length, and muscle explosiveness. And one form of training program that can be used to improve shooting results is circuit training.